MENINGKATKAN EKSPRESI EMOSI MELALUI KEGIATAN SENAM KREASI PADA ANAK KELOMPOK B DI TK MADINAH MALANG - Purnama Sahara, Leksi; Asmah, Ayu; Iswahyudi, Didik (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This research is motivated by the lack of optimal development of children's ability to express emotions. The purpose of this study was to improve the emotional expression skills of children in Group B. The research subjects were 14 children in Group B. The type of research used the Classroom Action Research (CAR) model. Data collection techniques used in this study were: observation, documentation, and performance assessment. The pre-action results obtained a 20% result. Then, the first cycle of research, meeting 1, obtained a percentage result of 62.49%, and in the second meeting, a result of 64.8%. The results of this study were said to have not met the learning completeness criteria. Therefore, a second cycle of research was needed. In the first cycle of cycle II, meeting 1, there was an increase of 73.25%, but this result was still categorized as incomplete because the result was <75%. A second cycle of cycle II was held to improve the results, and in the second cycle, there was an increase of 76.7%. The research stopped at the second cycle of cycle II meeting. Based on the results of the study, there was an increase in children's ability to express emotions. Therefore, it can be concluded that creative gymnastics can improve emotional expression in group B children at Madinah Kindergarten, Malang.   Keywords: Ability, Emotional Expression, Creative Gymnastics